Exposure variability of fosfomycin administered to pigs in food or water: Impact of social rank - Soraci, Alejandro Luis (2013)
The objective of this study was to document the effect of social ranking on the internal exposure of pigs to an antibiotic (fosfomycin) administered either in food or in drinking water. Signs of aggression were recorded at the feeder and drinker. The interindividual variability explained by the social rank was even greater when the test antibiotic was given in food despite the fact that the water consumption was less variable than the food intake. The range of plasma concentrations after administration of fosfomycin either in food or drinking water leads to a number of pigs in the treated group being exposed to rather low and highly variable concentrations of fosfomycin and not able to maintain adequate plasma concentrations above the typical minimum inhibitory concentration (MIC). Social rank clearly influences the level of exposure of pigs to fosfomycin both in food and drinking. However, its administration in drinking water is likely to be the best option to optimize antibiotic efficacy.